Relatórios de minorias com crianças e imagens: contornos de uma pesquisa margarida - Oliveira, Luana Priscila de [UNESP] (2015)
In the current context of research dealing with children and the production of images in education appear uncomfortable in relation to the act of searching, mainly because of the research subjects are, in this case children, who become protagonists of the research. Through the lens of equipment, these subjects/actors show us a world surrounded by compositions of bodies of focus and de-focus and other senses, sometimes even nonsense. Granddaughter perspective, authors such as Benjamin, Agamben, and Masschelein, dealing with the notion of experience, research as a tentative proceed, and the need for an education look and a poor pedagogy, respectively, bolster questions that deal with the ways of doing research in education with children and images, and also about the readings that become possible about the imagistic material produced by children and teachers in the context of everyday school life. In the face of such words and considering the last of the IM@go surveys: images Laboratory, experience and creation of campus UNESP Rio Claro, Department of Education, which has been dealing with the issue of research with children, teachers and image productions, and is also pursuing a another of researching mode, comes the interest of this master's research that permeates the question: What are the possibilities that present themselves when we take the prospect of doing research approaching the concepts of experience, poor pegadogia and heterotopia, based on the elaborations about these concepts according to Benjamin, Agamben, Masschelein and Foucault, respectively, to think about research with children and images in education? To this end, are utilized for the analysis imagery data (photos and footage) teachers and children, records made during the collections of images by the researcher and the students fellows, which bring testimonies of the teachers, children and the impressions of the researchers, in addition to literature review. Many ...